DEVELOPING COMMUNICATIVE COMPETENCE IN ENGLISH THROUGH TASK-BASED LANGUAGE TEACHING (TBLT) (SCIENCE TIME JOURNAL, 2026)
Task-Based Language Teaching (TBLT) is widely recognized as an effective learnercentered approach that develops communicative competence through meaningful, real-world tasks. This study investigates the impact of TBLT on university students’ communicative competence in English, focusing on speaking fluency, interaction skills, and learners’ confidence. An experimentel researchdesign was employed with a control group receiving traditional instruction and an experimental group receiving task-based instruction over a defined instructional period. Data were collected through preand post-speaking assessments, observation checklists, and learner questionnaires. The results indicate that students instructed through TBLT demonstrated noticeable improvement in fluency, interactional strategies (turn-taking, clarification requests, and negotiation of meaning), and willingness to communicate. The study concludes that TBLT creates a supportive environment for authentic language use and recommends its systematic integration into higher education English courses.